Hermite–Hadamard inequalities and their applications - Marcela V. Mihai; Muhammad Uzair Awan; Muhammad Aslam Noor; Jong Kyu Kim; Khalida Inayat Noor (Journal of Inequalities and Applications, 2018)
Abstract New Hermite–Hadamard type inequalities are established. Some corresponding examples are also discussed in detail.